Tuning the optical band gap of DH6T by Alq3 dopant - Fahmi Fariq Muhammad,; Khaulah Sulaiman, (Universiti Kebangsaan Malaysia, 2011)
Dihexyl-sexithiophene (DH6T) was doped with tris (8-hydroxyquinolinate) aluminum (Alq3) to prepare blends of DH6T/Alq3 by dissolving the mixture in the chloroform/hexane co-solvent. Solid films with different thickness deposited on quartz substrates were obtained from the blends via casting process. Optical absorption spectroscopy has been performed to measure the optical band gap of pure and doped DH6T as well as variations in the band gap with dopant concentration (weight %). This variation in optical band gap with dopant concentration was determined quantitatively with fitted and extrapolated techniques and observed qualitatively from the red shift appeared along the optical absorption spectra.The results showed that within a specific dopant content, the optical energy gap, Eg of DH6T decreases from 2.69 eV to 1.8 eV with increasing dopant concentration to 23.1%.